Facile preparation of amorphous iron nanoparticles filled alginate matrix composites with high stability. (6th October 2016) - Huang, Jian-Fei; Li, Yong-Tao; Wu, Jin-Hua; Dong, Xian-Ming; Cao, Piao-Yang; Liu, Yong-Lin; Lin, Zuan-Tao; Jiang, Gang-Biao
Abstract: Zero-valent iron nanoparticles have poor chemical stability due to their intrinsic crystal structure and surface energy that greatly limit their practical applications. However, significant improvements can be made via preparation of iron nanoparticles in amorphous structure. In this study, we provide a facile strategy to prepare amorphous iron nanoparticles filled alginate matrix composites. Sodium alginate, as the biopolymer matrix of the composites, can successfully inhibit the crystallization of iron nanoparticles and control their formation. In the presence of the alginate matrix, the amorphous iron nanoparticles can be prepared and act as the fillers of the composites. In the stability experiment, the air-exposed composites still remained 89.7% capability under the atmosphere with a relative humidity of 45% at 15 °C for 30 days. The result demonstrated that the amorphous iron nanoparticles of the composites exhibited high stability. Hence, the amorphous iron nanoparticles filled alginate matrix composites are very promising to be used in many fields.